Effect of Reinforcement Corrosion on Static and Dynamic Behaviour of RC Beams - Rattan, Anmol (My University, 2015)
Reinforced concrete structures have not been immune to the ravages of corrosion despite the protection that concrete provides to embedded steel. Since steel corrosion remains unnoticed inside the concrete, it further accelerates and can cause loss of life and property. This report discusses the effects of deterioration caused to reinforced beams due to corrosion at different levels and analyses the same by static and dynamic procedure. Four RC beams (127 x 227 x 4100 ) mm were cast one was kept as control beam and rest three of which were corroded to different levels i.e. (7days, 15days, 24days) by impressed current technique, while one remain as control beam . All four beams were subjected to vibration based health monitoring at the end of their respective corrosion period. This was done to investigate the effect of corrosion on dynamic properties of beams with increasing corrosion. Vibration characteristics of beams showed decrease in vibration amplitude and frequency of beam with increasing level of corrosion. After dynamic analysis ,each beam was tested under static four-point loading and corresponding loads and deflections were recorded. The static load deflection characteristics of beams corroded to different level shows decrease in load carrying capacity, deflection capacity with the increase in age of corrosion. Most importantly it was noticed that as corrosion increased the failure mode of beams shifts from predictable ductile failure to brittle failure.
M.E. (CED)
Keywords: corrosion; static properties; frequency; FRF; CED